Sustainable Operations and Closed-Loop Supply Chains - Souza, Gilvan C (Business Expert Press, 2012)
Ebook from IG Library ; This book was written for any company or organization that needs detailed guidance on the journey towards sustainability, starting from zero. And if your firm wants to be sustainable, you know you have to consider the triple bottom line when making decisions: economic (profit), environmental (planet), and social (people). By focusing on the triple bottom line (3Ps), your firm can be assured of a steady supply of inputs such as raw materials and labor.